Legal Education in the 21st Century Nigeria: Need for Diversity in Content Paradigm - Ikpeze, Ogugua V.C. (2015)
Many aspects of education including legal education are driven by new market dynamics of demand and supply.The old adage remains that law is an instrument of social engineering, and the addendum is that lawyers are part and parcel of agents of social engineering resulting to change. Therefore legal education must diversify for Law, law students and lawyers to impact positively in today’s world. Perhaps these concepts explain the ever growing course content, in the current legal education curriculum. This paper seeks to: 1. examine the previous course content in legal education and the current courses as well as the frequency of assessment. 2. The impact of present curriculum modalities for legal education and 3. Effects of innovations in legal education on Nigerian lecturers, students and society at large. The methodology is based on literature review, classroom experience, and societal reactions to lawyers and public interest lawyer-ring. It examines whether there is adequate diversification of courses for legal education in Nigeria and what needs to be done to effectively maintain relevance of law and the legal professional within and outside the Nigerian society. Key words: Legal education, Nigeria, content diversit